Pre- and post-cooking quality characteristics of drought tolerant upland rice - Mishra, Ashok; Bagchi, T B; Sharma, S G; Mukherjee, A K; Kar, Meera K (ORYZA-An International Journal of Rice, 2018)
Rice grains of 24 genotypes were examined for various pre-cooking traits like hulling %, milling %, head rice recovery (HRR %), moisture %, length (mm), breadth (mm) and length : breadth ratio; and post-cooking traitslike kernel length (mm) after elongation, volume expansion ratio, elongation ratio, amylose content and water uptake on cooking. Among the test genotypes, both hulling and milling % were found to be the lowest in one scented genotype, ODR 1-3 (72.5% and 60%, respectively) and highest in ODR 5 (81% and 68%, respectively). Hulling % was found to bear strong positive correlation with milling %. Head rice recovery, which is mostly valued by the consumers, ranged from 38% in ODR-12-1 to 59.5% in ODR 2. Lowest grain breadth (1.47mm)along with highest grain length (6.85 mm) and length: breadth ratio (4.66) was observed in ODR 1-1. Other genotypes with length: breadth ratio above 4.0 were ODR 1-3 (4.25), ODR 1 (4.20) and ODR 1-2 (4.10). All these four genotypes were aromatic. Highest amylose content of 26.21 % was recorded in ODR-58. Grain length was strongly associated with length : breadth ratio and kernel length after cooking but negatively associated with breadth. 24 rice genotypes fell into two clusters based on their dissimilarity with respect to different quality characters.